SEW: Looking for a definition and controversial issues - Martínez-Romero, M. José; Rojo-Ramírez, Alfonso Andrés (European Journal of Family Business, 2016)
This paper analyses the Socioemotional Wealth (SEW) theory to manage a better comprehension of this relatively new approach. For achieving our objective, we review previous research about SEW and gather all the given definitions of this term. We also make our own conceptualization of it. Moreover, we discuss three controversial issues related to this approach: the relationship between SEW and Emotional Value, situations that could lead to different SEW levels, and the effects of ownership and management in the SEW of a family firm. Finally, we point out the principal challenges it poses for researchers.